Factors affecting the demand of Malaysian palm oil / Sayang Zulina Zuikarnain (Faculty of Business and Management, 2008)
Palm oil is one of the agricultural products in Malaysia that provide a lot of potential in the economic growth. Malaysia had been one of the major producer and exporter of palm oil. The demand of palm oil had increase by time. The volatility in palm oil prices is a significant risk to producers, traders, consumers and others involved in the production and marketing of palm oil. Malaysia's palm oil industry also is not only free of subsidy but pays a substantial direct income to the State through numerous taxes, fees and levy payments. This research studies on factors affecting the demand of Malaysian palm oil. Palm oil in Malaysia faced many problems. The main objective of this study is to determine the factors that influenced the demand of Malaysian palm oil. In order to conduct this study, secondary data (time series) was used. The factors that affect the demand of Malaysian palm oil were highlighted and all of the variables were examined by using the Ordinary Least Square method (OLS), and Multiple Regression model (MR). Factors such as palm oil prices, population, economic growth and soybean oil prices had been identified. The result showed that three of the independent variables are significant. The factors are palm oil prices, population and soybean oil prices.